2018
DOI: 10.1101/465708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Transcriptome and Methylome Analysis in Human Skeletal Muscle Anabolism, Hypertrophy and Epigenetic Memory

Abstract: 38Transcriptome wide changes in human skeletal muscle after acute (anabolic) and chronic resistance exercise 39 (RE) induced hypertrophy have been extensively determined in the literature. We have also recently 40 undertaken DNA methylome analysis (850,000 + CpG sites) in human skeletal muscle after acute and 41 chronic RE, detaining and retraining, where we identified an association between DNA methylation in an 42 epigenetic memory of exercise induced skeletal muscle hypertrophy. However, it is currently unk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 75 publications
2
40
0
Order By: Relevance
“…A recent study also supported the role of UBR5 as being essential for muscle growth through RNAi screening in Drosophila larvae, where UBR5 inhibition led to smaller sized larvae (Hunt et al, 2019). Finally, unpublished data from our lab in bioengineered mouse SkM also demonstrated that UBR5 was the most significantly upregulated transcript after loading, amongst a selection of genes that are known to be regulated across the human transcriptome and methylome after acute RE (Seaborne et al, 2018b;Turner et al, 2019b). Collectively, these data support the notion that UBR5 is involved in load-induced anabolism and hypertrophy, in contrast with the well-known MuRF1 and MAFbx E3 ligases that are associated with muscle atrophy.…”
Section: Introductionmentioning
confidence: 54%
“…A recent study also supported the role of UBR5 as being essential for muscle growth through RNAi screening in Drosophila larvae, where UBR5 inhibition led to smaller sized larvae (Hunt et al, 2019). Finally, unpublished data from our lab in bioengineered mouse SkM also demonstrated that UBR5 was the most significantly upregulated transcript after loading, amongst a selection of genes that are known to be regulated across the human transcriptome and methylome after acute RE (Seaborne et al, 2018b;Turner et al, 2019b). Collectively, these data support the notion that UBR5 is involved in load-induced anabolism and hypertrophy, in contrast with the well-known MuRF1 and MAFbx E3 ligases that are associated with muscle atrophy.…”
Section: Introductionmentioning
confidence: 54%
“…Human muscle cells were isolated from the vastus lateralis biopsies of three healthy young adult males (28 ± 11 years, 73.00 ± 0.91 kg, 177.2 ± 4.3 cm, mean ± SD) that were recreationally active but had never undergone a period of supervised chronic aerobic or resistance exercise. The full biopsy procedure and the primary cell isolation procedures have been described previously (Seaborne et al 2018a;Seaborne et al 2018b;Turner et al 2019a;Turner et al 2019b). Ethical approval was granted by the NHS West Midlands Black Country, UK, Research Ethics Committee (NREC approval no.…”
Section: Human Muscle Biopsies Cell Isolation and Differentiation Inmentioning
confidence: 99%
“…We shared one CpG site in each of the loading and unloading phase, with both CpGs located in the intergenic region ( Table S5A). We further compared our CpGs with those identified by Turner et al ., 34 who analysed transcriptome and methylome associations after acute/chronic resistance training, but no common CpG was found. Notably, Turner et al .…”
Section: Discussionmentioning
confidence: 99%